Autophagy mediates phosphatidylserine exposure and phagosome degradation during apoptosis through specific functions of GABARAP/LGG-1 and LC3/LGG-2. Issue 2 (1st February 2019) - Jenzer, Céline; Simionato, Elena; Largeau, Céline; Scarcelli, Vincent; Lefebvre, Christophe; Legouis, Renaud
ABSTRACT: Phagocytosis and macroautophagy/autophagy are 2 processes involved in lysosome-mediated clearance of extracellular and intracellular components, respectively. Recent studies have identified the recruitment of the autophagic protein LC3 during phagocytosis of apoptotic corpses in what is now called LC3-associated phagocytosis (LAP). LAP is a distinct process from autophagy but it relies on some members of the autophagy pathway to allow efficient degradation of the phagocytosed cargo. We investigated whether both LC3/LGG-2 and GABARAP/LGG-1 are involved in phagocytosis of apoptotic corpses during embryonic development of Caenorhabditis elegans . We discovered that both LGG-1 and LGG-2 are involved in the correct elimination of apoptotic corpses, but that they have different functions. lgg-1 and lgg-2 mutants present a delay in phagocytosis of apoptotic cells but genetic analyses indicate that LGG-1 and LGG-2 act upstream and downstream of the engulfment pathways, respectively. Moreover, LGG-1 and LGG-2 display different cellular localizations with enrichment in apoptotic corpses and phagocytic cells, respectively. For both LGG-1 and LGG-2, subcellular localization is vesicular and dependent on UNC-51/ULK1, BEC-1/BECN1 and the lipidation machinery, indicating that their functions during phagocytosis of apoptotic corpses mainly rely on autophagy. Finally, we show that LGG-1 is involved in the exposure of the 'eat-me signal' phosphatidylserine at the surface of the apoptotic cell to allow its recognition by the phagocytic cell, whereas LGG-2 is involved in later steps of phagocytosis to allow efficient cell corpse clearance by mediating the maturation/degradation of the phagosome.